The impact of affiliate marketing on the purchase behavior of Gen Z private school students in Tacloban City - Marsan, Pearlene Dawn G.; Ronato, Tiffany Grace M.; Tejones, Nickson Andrew G.; Sudario, Marla B. (Tacloban City Division of Management, University of the Philippines Tacloban College, 2025)
Affiliate marketing is a growing digital strategy that leverages influencers and content creators to promote products and services in exchange for commissions. As digital platforms evolve, businesses are increasingly targeting Generation Z, a demographic known for its strong online presence and significant purchasing power. This study examined the impact of affiliate marketing on the consumer behavior of Generation 2. private school students in Tacloban City, focusing on the effects of information, entertainment, and trust dimensions on consumer engagement and purchase intentions. The researchers employed a descriptive correlational research design. Data were collected through a survey questionnaire administered both online and face-to-face among 150 Gen Z private school students in Tacloban City. Results revealed that the information and entertainment dimensions of affiliate marketing content strongly influenced consumer behavior and purchase intention, while trust was a weaker factor due to a degree of skepticism. Contributory and passive behaviors were the most common modes of engagement, with students relying on social proof but showing low active participation. The study concludes that informative and entertaining affiliate content significantly shapes Gen Z's purchasing behavior, although trust remains a barrier to full engagement. The researchers recommend that future studies explore strategies to enhance credibility and authenticity in affiliate marketing, particularly among digital-native audiences.
Undergraduate thesis (Bachelor of Science in Accountancy) -- University of the Philippines, Tacloban.
Keywords: Social media marketing -- Tacloban City; Consumer behavior -- Tacloban City